Pengetahuan, Sikap dan Status Remaja Putri terkait Kurang Energi Kronik (KEK) di SMAN 2 Mamuju - Hasanah, Uswatun; Nurbaya, Nurbaya; Najdah, Najdah; Irwan, Zaki; Dzulifsal Al-Fath, Muhammad (Mando Care Jurnal, 2025)
Chronic Energy Deficiency (CED) among adolescent girls is a serious concern due to its long-term implications for reproductive health. This study aims to describe the knowledge, attitudes, and nutritional status of adolescent girls regarding CED at SMAN 2 Mamuju. A descriptive survey method with a quantitative approach was employed. The sample consisted of 165 female students from grades X and XI, selected through proportional simple random sampling. Data collection was conducted using questionnaires and anthropometric measurements, including Body Mass Index for Age (BMI/Age) and Mid-Upper Arm Circumference (MUAC). The results showed that the majority of respondents had moderate knowledge (50.9%) and a positive attitude (97.6%) toward CED. Nutritional status based on BMI/Age indicated that most adolescents had good nutritional status (81.2%), whereas MUAC measurements revealed that 47.9% were at risk of CED. These findings highlight a discrepancy between knowledge and positive attitudes versus actual practices in maintaining proper nutrition among adolescent girls. Continuous, practice-based nutrition education involving schools, healthcare providers, and families is needed to reduce the prevalence of CED in this population.